Islamic Law and Legal System : Studies of Saudi Arabia - Vogel, Frank, (Brill Book Archive Part 1, ISBN: 9789004472495., 2000)
Based on years of research in Saudi Arabia, this volume investigates the legal system of Saudi Arabia both for its own sake and as a case-study of an Islamic legal system. As a study of Saudi Arabia, it is the first extensive treatment in English of the constitution and Islamic court system of Saudi Arabia. As a study of an existing legal system in continuity with past Islamic law and practice, it sheds new light on Islamic legal doctrine, practice, and institutions, correcting for past scholarly neglect of Islamic law's application. The book develops a framework of concepts, rooted in both Islamic and western legal theory, useful for the comparative description and analysis of Islamic legal systems and applications, past and present.